Pengaruh Anggaran Beban Operasional dan Anggaran Pendapatan sebagai Alat Perencanaan dan Pengendalian terhadap Kinerja Keuangan pada PT Wakaf Pro Corpora - Cahyani, Dzurriyati; Burhany, Dian Imanina; Dahtiah, Neneng (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
This study aims to analyze the influence of operational expense and revenue budget as planning and control tools on the financial performance of PT Wakaf Pro Corpora during the 2022-2024 period. As a startup company established only three years ago, the company faces challenges in budget management to support the achievement of optimal financial performance. This research employs a quantitative approach, utilizing secondary data in the form of financial reports and company budgets for the selected periods. The independent variables include operational expense budget and revenue budget, functioning as planning and control tools. As a planning tool, budget is measured by budget amount, while as a control tool, budget is measured by budget variance ratio. The dependent variable is financial performance measured by the net profit margin (NPM) ratio. The findings reveal that the operational cost budget as a planning tool has no significant effect on financial performance, while the revenue budget as a planning tool has a significantly positive effect. Furthermore, the operational cost budget as a control tool has a significantly negative effect, while the revenue budget as a control tool has a significantly positive effect on financial performance. The simultaneous test shows that budgets, as both planning and control mechanisms, have a significant impact on financial performance. These results convey the important message of the role of the budget as a planning and control tool to help achieve the company's financial performance.